Intracerebral Transplantation of Differentiated Human Embryonic Stem Cells to Hemiparkinsonian Monkeys. Issue 5 (May 2013) - Emborg, Marina E.; Zhang, Zhijian; Joers, Valerie; Brunner, Kevin; Bondarenko, Viktorya; Ohshima, Sachiko; Zhang, Su-Chun
To explore stem cell therapy for Parkinson's disease (PD), three adult rhesus monkeys were first rendered hemiparkinsonian by unilateral intracarotid 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) infusion. Five months postinfusion, they were given MRI-guided stereotaxic intrastriatal and intranigral injections of green fluorescent protein (GFP)-labeled cultures of dopaminergic neurons derived from human embryonic stem cells (DA-hES cells). The animals were immunosuppressed using daily oral cyclosporine (CsA). Three months later, viable grafts were observed at the injection sites in one animal, while no obvious grafts were present in the other two monkeys. The surviving grafts contained numerous GFP-positive cells that were positively labeled for nestin and MAP2 but not for glial fibrillary acidic protein (GFAP), NeuN, or tyrosine hydroxylase (TH). The grafted areas in all animals showed dense staining for GFAP, CD68, and CD45. These results indicated that xenografts of human stem cell derivatives in CsA-suppressed rhesus brain were mostly rejected. Our study suggests that immunological issues are obstacles for preclinical evaluation of hES cells and that improved immunosuppression paradigms and/or alternative cell sources that do not elicit immune rejection are needed for long-term preclinical studies.